2014
DOI: 10.1371/journal.pone.0097743
|View full text |Cite
|
Sign up to set email alerts
|

CARP Is a Potential Tumor Suppressor in Gastric Carcinoma and a Single-Nucleotide Polymorphism in CARP Gene Might Increase the Risk of Gastric Carcinoma

Abstract: BackgroundThe caspase-associated recruitment domain-containing protein (CARP) is expressed in almost all tissues. Recently, the tumor-suppressive function of CARP was discovered and attracted increasing attention. This study aimed to investigate the role of CARP in the carcinogenesis of human gastric carcinoma.Methodology/Principal FindingsCompared with normal gastric tissue, the downregulation of CARP expression was observed in gastric carcinoma tissue by cDNA array and tissue microarray assay. In vitro, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It was also demonstrated that CARP-1 and zyxin cooperate to promote apoptosis [26] . CARP-1 was found to be downregulated in 63% of gastric cancer tissues; of which, low-intensity staining was identified in 81% cases while no patients with gastric cancer had a high-intensity staining for CARP-1 [27] . Another study on zyxin found that it is downregulated in Ewing sarcoma where zyxin is more concentrated in the cytoplasm rather than cell adhesion junctions.…”
Section: Introductionmentioning
confidence: 95%
“…It was also demonstrated that CARP-1 and zyxin cooperate to promote apoptosis [26] . CARP-1 was found to be downregulated in 63% of gastric cancer tissues; of which, low-intensity staining was identified in 81% cases while no patients with gastric cancer had a high-intensity staining for CARP-1 [27] . Another study on zyxin found that it is downregulated in Ewing sarcoma where zyxin is more concentrated in the cytoplasm rather than cell adhesion junctions.…”
Section: Introductionmentioning
confidence: 95%
“…Another example is MINDY3 in prostate cancer; MINDY3 codes for a protein that contains a caspase-associated recruitment domain and may be involved in apoptosis ( Safran et al 2010 ). Even though it has been identified as a tumor suppressor in lung and gastric cancers ( Lu et al 2014 ), our study is the first to link it with prostate cancer. For the same cancer type, prostate cancer, we find C9orf72, a gene that has been associated with several neurodegenerative disorders ( McCauley et al 2020 ).…”
Section: Resultsmentioning
confidence: 82%
“…Overexpression of zinc finger, DHHC-type containing 14 (ZDHHC14) promotes the migration and invasion of scirrhous GC (4). Caspase-associated recruitment domain-containing protein (CARP) is a potential tumor suppressor in GC, and a single-nucleotide polymorphism in the CARP gene may increase the risk of GC (5). Ras association domain family member 10 (RASSF10) is an epigenetically silenced tumor suppressor in GC (6).…”
Section: Introductionmentioning
confidence: 99%
“…Ras association domain family member 10 (RASSF10) is an epigenetically silenced tumor suppressor in GC (6). It has previously been demonstrated that the inactivation of tumor suppressor genes and activation of oncogenes serve a significant role in carcinogenesis (3)(4)(5)(6). However, the etiology of GC remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%